METODE MANUAL PADA PEMBONGKARAN JEMBATAN RANGKA BAJA ROBOH - Surya Adinata (JURNAL PLANOLOGI DAN SIPIL (JPS), 2019)
The bridge is a complementary road building whose existence is indispensable as an infrastructure for the movement of goods and services that connects road segments which are cut off by various conditions due to very crowded rivers, valleys, and land transportation. The location was done on the Sungai Tiu, Lubuk Jambi - Pucuk Rantau, Kuantan Singingi. The bridge of type C of Sungai Tiu previously was built firmly, but now was broken and collapsed, so that all components of the bridge will be dismantled. The collapse of this bridge is because the bridge is not able to support heavy of vehicles loaded with coal of loads exceed the maximum carrying capacity of 55 tons. The process of dismantling the bridge components is done manually, because mechanical disassembly using heavy equipment is not possible and too expensive. The Directors of bridge demolition activities are the Public Works and Public Housing Agency and its contractor, PT. Usaha Kita Abadi. The purpose of this study is to see how effective the Manual Method by using simple tools in dismantling building structures over the steel frame bridge. The components of the bridge to be demolished as follows: backrest / fence (Handrail), wind bond (Upper Bracing), portal, top edge rod (Top chord), diagonal rod, floor, elongated girder (Stringer), transverse girder (Cross Beam) ) and bottom edge rod (Bottom Chord). The equipments used are: Meters, welds, Hammers, Binding tools and pullers, Shock / Fitting Ring Keys, Drop Hammer, Pulley wheels, and Lier (Winch) Pulling Tools. Demolition of the Steel Frame Bridge (Upper Building) with the Manual Method include: Handrail demolition, Upper Bracing, Portal demolition work, Top chord demolition, Diagonal rod demolition work , Bridge floor demolition work, Elongated girder (Stringer) demolition work, Cross Beam demolition work, Bottom Chord demolition work. The demolition of the building on Sungai Tiu bridge which has collapsed by Manual Method on the form of simple equipment utilization has effectively managed to evacuate the upper parts of the bridge